Bhabinkamtibmas Efforts in Preventing the Spread of Radical Understanding in the Legal Territory of the Tegal Resort Police - Rinal Krishna Triananda (Police Studies Review, 2021)
This study examines the efforts of Bhabinkamtibmas in preventing the spread of radicalism. This study has a research focus, namely "Efforts of Bhabinkamtibmas in Preventing the Spread of Radical Understanding in the jurisdiction of the Tegal Police" because the capabilities possessed by Bhabinkamtibmas are the spearhead of the Police in the field of prevention in preventing the spread of radical ideas in society through sambang, guidance and counseling. There are three issues raised in this thesis research, namely about; (1) What are the efforts of Bhabinkamtibmas to prevent the spread of radical ideas? (2) What are the factors that hinder the implementation of Bhabinkamtibmas' duties? (3) How to improve the capabilities of Bhabinkamtibmas? To analyze the three problems, the researcher used the field and research method with a qualitative approach. The use of a conceptual framework in the form of theories and concepts is used as an analytical knife by researchers in answering the predetermined problem formulation. Theories and concepts used by the researcher are management theory, 6 M management theory, competency theory, Polmas concept, Bhabinkamtibmas concept, and Radicalism concept. The findings of this study are (1) Bhabinkamtibmas in an effort to prevent the spread of radicalism has a very vital role where in efforts to prevent the spread of radicalism Bhabinkamtibmas is required to be able to provide understanding to the wider community about the dangers of radicalism and how to counteract and prevent this understanding. (2) Obstacles to the task of Bhabinkamtibmas are internal factors originating from within the Polri organization itself and external factors originating from outside the Polri organizational environment. (3) The ability of Bhabinkamtibmas in the fields of knowledge, skills/ability, and behavior requires improvement. The results of the findings of researchers in the field, the authors suggest that Bhabinkamtibmas training be carried out in all fields, both in the police and non-police fields as well as skills and abilities in the field of technology in supporting efforts to prevent the spread of radicalism in the jurisdiction of the Tegal Police.